1995
DOI: 10.1111/j.1540-8159.1995.tb06741.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nuclear Magnetic Resonance Imaging on Cardiac Pacemakers

Abstract: Patients with cardiac pacemakers are currently restricted from nuclear magnetic resonance imaging (MRI). The aim of the study was to analyze the influence of MRI on new generation pacemakers. Tests were performed using a phantom model with seven dual chamber and two single chamber systems in a 0.5 Tesla MRI scanner. Monitoring by telemetry and oscillography were used during the standard clinical scan sequences as well as a pacemaker inquiry after each sequence. Spin echo, gradient echo, and fast field echo seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…It was shown that radiofrequency fields could inhibit demand pacing and time-varying magnetic fields could generate pulse amplitudes and mimic cardiac activity. Additional in vitro studies ranging from 0.15T to 0.5T revealed no adverse effects, but the studies also confirmed that the demand mode can revert to a reversible asynchronous mode when exposed to the static field because of reed switch closure [5,6]. Pacing systems already programmed to asynchronous mode did not appear to be susceptible to heart stimulation or inhibition.…”
Section: In Vitro Datasupporting
confidence: 63%
“…It was shown that radiofrequency fields could inhibit demand pacing and time-varying magnetic fields could generate pulse amplitudes and mimic cardiac activity. Additional in vitro studies ranging from 0.15T to 0.5T revealed no adverse effects, but the studies also confirmed that the demand mode can revert to a reversible asynchronous mode when exposed to the static field because of reed switch closure [5,6]. Pacing systems already programmed to asynchronous mode did not appear to be susceptible to heart stimulation or inhibition.…”
Section: In Vitro Datasupporting
confidence: 63%
“…Cardiac pacemakers present potential problems to patients undergoing MR procedures from several mechanisms, including: 1) movement of the pacemaker (implantable pulse generator and/or leads) due to the strong static magnetic field of the MR system; 2) MRIrelated heating of the pacemaker lead by the time-varying fields; 3) inhibition or modification of the function of the pacemaker by the electromagnetic fields used for MRI; and 4) inappropriate or rapid pacing due to pulsed gradient magnetic fields and/or pulsed radio frequency (RF) fields (i.e., electromagnetic interference) from the operating MR system (i.e., with the pacing lead acting as an antenna) (4,5,8,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). These problems may result in serious injuries or lethal consequences for patients.…”
Section: Mr Safe Fiber-optic Cardiac Pacing Leadmentioning
confidence: 99%
“…The investigators of these studies and others have also suggested certain strategies for performing safe MRI procedures. These strategies included programming the pacemaker device subthreshold (13,18,19,21) or to asynchronous mode (3,9,11,13,22,27), programming to a bipolar lead configuration if possible (13,26), only imaging non-pacemaker-dependent patients (13,25), limiting exposure to RF power during MRI (9,13,19), and only performing MRI examinations if the pulse generator is positioned outside of the bore of the MR system (20). Some have even favored explanting the pulse generator prior to MRI (28).…”
mentioning
confidence: 98%